1.25 Gbits/s-message experimental transmission utilising chaos-based fibre-optic secure communications over 143 km. (8th May 2019) - Yin, Hongxi; Zhao, Qingchun; Xu, Dongjiao; Chen, Xiaolei; Chang, Ying; Yue, Hehe; Zhao, Nan
Chaotic optical secure communications (COSC) are a kind of fast-speed hardware encryption technique at the physical layer. Concerning the practical applications, high-speed long-haul message transmission is always the goal to pursue. In this paper, we report experimentally a scheme of long-haul COSC, where the bit rate reaches 1.25 Gbits/s and the transmission distance up to 143 km. Besides, a distinct advantage of low-cost is guaranteed with the off-the-shelf optical components, and no dispersion compensating fibre (DCF) or forward-error correction (FEC) is required. To the best of our knowledge, this is the first experimental evidence of the longest transmission distance in the COSC system. Our results show that high-quality chaotic synchronisation can be maintained both in time- and frequency-domain, even after 143 km transmission; the bandwidth of the transmitter is enlarged by the external optical injection, which leads to the realisation of 2.5 Gbits/s-message secure transmission up to 25 km. In addition, the effects of device parameters on the COSC are discussed for supplementary detail.